The Effect Locus of Control and Organizational Culture Toward Employee Performance with Organizational Commitments as Intervening Variable - Sitti Rizki Mulyani; Marta Widian Sari; Vivi Nila Sari; Winda Tawakalni (University of Islam Malang, 2019)
This study aims to examine the influence of locus of control and organizational culture toward employee performancewith organizational commitment as an intervening variable.The use of organizational commitment as a predictor in evaluating employee performances makes this research different from all other research. The source of data from this study was obtained from primary data by distributing questionnaires with sample size target is 141 employees. The analytical method used in this study is multiple regression analysis and path analysis. The results of this study indicate that there is a direct relationship between locus of control and organizational culture toward organizational commitment and employee performance.Also, there is an indirect effect between locus of control and organizational culturetoward employee performance with organizational commitment as an intervening variable.